EFEKTIFITAS PEMBELAJARAN MENGGUNAKAN KIT OPTIK MELALUI PENDEKATAN SAINTIFIK DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMA PADA MATERI OPTIKA GEOMETRI - Risna, Novia Yunanda; Azhar, Azhar; Irawan, Dedi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract. In Indonesia, physics abilities nationally and internationally are decreasing every year, resulting in students' critical thinking abilities also decreasing. One of the supporting factors that can be done by physical teachers is the use of learning tools/media such as Optical KITs in the learning process, especially Physics. This research aims to describe students' critical thinking abilities with the effectiveness of the Optical KIT in optics material. The Quasi-Experimental Method utilizes the Pst-test only non-equivalent control group design used in this research. The sample for this research was 56 students in class XI Science at SMAN 1 Kubu Babussalam. Data was obtained through a post-test, a total of 20 objective questions which were analyzed descriptively and inferentially to find out how students' critical thinking abilities use the SPSS version 25 application. implementation of Optical KIT. The results of inferential analysis on the t-test using SPSS version 25 with significant results of 0.014 <0.05, meaning that Ho is not rejected and Ha is rejected. So in conclusion, critical thinking skills experience significant differences between classes that apply KIT Optical learning media and classes that do not apply KIT Optical learning media. This means that the Optical KIT learning media on geometric optics material is effectively used so that the critical thinking skills of students at SMAN 1 Kubu Babussalam increase.Keywords: Optical KIT, Critical Thinking Ability, Geometry Optik